An Analysis of Organizational Culture on Employee Performance - Heskyel Pranata Tarigan (Utami Publisher, 2026)
Organizational culture is a strategic factor that plays a role in shaping employee behavior and performance. This study aims to analyze the influence of organizational culture on employee performance at the Institute for Publication, Journal Development, Publishing, and Intellectual Property Rights (LPPJPHKI) at Dehasen University in Bengkulu using the binary logit regression method. The research approach used was quantitative with a survey technique. The research population consisted of all LPPJPHKI employees, with a sample size of 60 respondents. Data were collected through a structured questionnaire and analyzed using logistic regression. The results indicate that organizational culture significantly influences employee performance with a significance level of < 0.05. These findings suggest that strengthening organizational culture can increase the probability of employees achieving high performance. This study provides strategic recommendations for LPPJPHKI management to improve employee performance through the strengthening of organizational culture.